2011
DOI: 10.1080/15228835.2011.587737
|View full text |Cite
|
Sign up to set email alerts
|

Audience Response Systems: Using “Clickers” to Enhance BSW Education

Abstract: Among new technologies for enhancing classroom-based education are audience response systems (ARS), also known as ''clickers.'' These handheld devices record student responses to instructor questions and send them electronically to a receiver that tallies the responses. Summary results are then projected, usually as a graph. Instructors piloted the use of clickers in undergraduate social work research and practice courses. Instructor and student experiences with the clickers were examined by type of course, fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Some of these factors were echoed in the ways that their course lessened their anxiety, such as making the content relevant and engaging students with clickers. Clickers encourage students to pay attention and actively participate, without the embarrassment of getting a question wrong or admitting not knowing an answer (Smith, Shon, & Santiago, 2011), which is important within a class where many students report anxiety and lack of confidence with the material. Clickers provide immediate feedback and are a technologically savvy version of the classroom assessment technique that Goldstein (2007) encouraged in introductory statistics courses.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these factors were echoed in the ways that their course lessened their anxiety, such as making the content relevant and engaging students with clickers. Clickers encourage students to pay attention and actively participate, without the embarrassment of getting a question wrong or admitting not knowing an answer (Smith, Shon, & Santiago, 2011), which is important within a class where many students report anxiety and lack of confidence with the material. Clickers provide immediate feedback and are a technologically savvy version of the classroom assessment technique that Goldstein (2007) encouraged in introductory statistics courses.…”
Section: Discussionmentioning
confidence: 99%
“…A well-designed written communication will engage the audience and facilitate comprehension, but the ease of completing the behavior will also influence compliance rates. Audiences prefer "easy" behaviors (Smith, Shon, and Santiago 2011), which are generally those within their personal capabilities, knowledge, and skill sets (Michie, van Stralen, and West 2011). Complex requests should therefore be divided into simpler, smaller tasks with a low "hassle factor" (Behavioural Insights Team 2014).…”
Section: Easementioning
confidence: 99%
“…Interestingly, MacGeorge  et al 7 highlighted that anxiety regarding the initial use of CRS exists in lecturers as well as students, with Walklet  et al 8 emphasising that additional planning time may be required when utilising CRS. Additionally, Bunz9 and Smith  et al 10 suggested that a more simplified system with streamlined features may offer greater ease at the point of use; Graham  et al 11 added that increased lecturer experience with the technology may facilitate the integration of CRS more effectively into the teaching programme. The studies concerned with ‘cloud’-based CRS platforms suggested that the complexity was centred around appropriate setting of questions, rather than use of the platforms themselves 12 13…”
Section: Introductionmentioning
confidence: 99%